Animal Waste Processing Technology And Poultry Farming In Organomineral Fertilizers - Uktam, Temirov; Shafoat, Namazov; Akhmedovna, Reymov; Najimuddin, Usanbaev; Azamat, 5Orakbaev (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of a study of the processes of obtaining organic fertilizers by composting and accelerated methods based on manure of cattle, poultry manure and substandard phosphorites, which is a waste of enrichment of phosphorites of the Central Kyzyl Kum, as well as the results of agrochemical tests of the resulting organic fertilizers. It is shown that, when composting cattle manure with the addition of substandard phosphorites with an increase in composting duration in all ratios, the formation of humic substances and assimilable phosphorus compounds for plants increase in all ratios, with an increase in the amount of substandard phosphorites in composts, the loss of organic substances and nitrogen is significantly reduced, and the degree of conversion of organic parts of manure in humic substances, the possibility of obtaining nitrogen- phosphorus-humic fertilizers is also shown eny bird droppings by acidification with nitric acid and subsequent decomposition of substandard phosphate using nitric acid-bird droppings.